2021
DOI: 10.1126/sciadv.abg0811
|View full text |Cite
|
Sign up to set email alerts
|

Virus self-assembly proceeds through contact-rich energy minima

Abstract: Single-molecule fluorescence optical tweezers studies combined with high-speed AFM reveal early events in the HBV life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 76 publications
4
18
0
Order By: Relevance
“…Trajectories that form such an intermediate will go on to form either T =4 capsids or malformed structures, whereas trajectories that diverge from the T =4 pathway before forming a complete T =4 dodecamer form either T =3 capsids or malformed structures. This prediction is consistent with recent AFM observations of HBV capsid protein assembly [33]. Knowledge of hub states could suggest new antiviral drug targets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Trajectories that form such an intermediate will go on to form either T =4 capsids or malformed structures, whereas trajectories that diverge from the T =4 pathway before forming a complete T =4 dodecamer form either T =3 capsids or malformed structures. This prediction is consistent with recent AFM observations of HBV capsid protein assembly [33]. Knowledge of hub states could suggest new antiviral drug targets.…”
Section: Discussionsupporting
confidence: 92%
“…The T =4 dodecamer was identified as a frequently observed intermediate along T =4 assembly pathways in AFM measurements of HBV dimers assembling on a mica plate [33]. The significance of this structure to formation of T =4 capsids in our simulations qualitatively agrees with this observation.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Resolving the empty capsid assembly mechanism is already a very challenging problem, [24][25][26][27][28][29][30][31][32][33] despite recent progress with experimental techniques such as resistive pulse sensing , 34,35 mass spectrometry, 36 charge detection mass spectrometry, [37][38][39][40] and solution small-angle Xray scattering (SAXS). [41][42][43][44][45][46][47] Our lab, however, developed a robust and transparent mechanism for isolating the most probable intermediates at equilibrium and on the assembly path of an empty Hepatitis B capsid. 48 Using MC simulations, we created a library of representative intermediates and showed that at equilibrium a very limited number of relevant assembly reaction products were selected based on their Boltzmann weights, computed from the self-association standard free energy between subunits.…”
Section: Introductionmentioning
confidence: 99%